THE THEORY OF “UNIVERSAL PEACE” IN THE WORKS OF MAWLANA JALAL AL-DIN BALKHI (RUMI) - Jumakulov Jamshid Panjievich (Western European Studies, 2025)
This article discusses the theory of “Universal Peace” in the works of Mawlana Jalal al-Din Rumi and acquaints the reader with the meaning and essence of the poet’s love-filled and humanistic poetry. The poet considers the word “Love” as the axis of human peace and friendship, and he strived to eliminate hatred and hostility among people, leading them toward true unity and harmony.
Keywords: Jalal al-Din Rumi; Masnavi-ye Ma‘navi; Diwan-e Shams